Analisis pengukuran hasil ulangan menggunakan teori tes klasik dan model Rasch pada siswa SMA - Annisa El Hasna (Bio-Pedagogi : Jurnal Pembelajaran Biologi, 2025)
ENEvaluation is an important part and stage that educators must go through to ensure effective learning. Evaluation results can be used as material for teacher reflection in developing and organizing learning programs and activities. The research aims to compare the analysis of assessment or evaluation using Classical Test Theory with the Rasch model and can find out the differences in analysis using the two models. The type of research in this study is a qualitative method with a descriptive approach. The sample used is the results of the Virus Chapter daily test with a total of 15 questions. Assessment analysis based on classical test theory using Microsoft Excel application and assessment analysis based on Rasch Model using Winsteps Rasch application. Validity analysis on classical test theory and Model Rasch amounted to nine valid questions and six invalid questions, and five valid questions and 10 invalid questions. Reliability test analysis through classical test theory obtained a value of 0.672 with a moderate category and from Item Reliability obtained a value of 0.87 with a good category. The average difficulty level of questions on the test theory is 0.463 at a moderate level, according to the Rasch Model there are three very easy questions, five easy questions, three difficult questions, and four very difficult questions. Analysis of distinguishing power based on classical test theory which is in the bad category of one item, six items are sufficient, five items are high, and three items are very high. The distinguishing power of items based on the Rasch Model obtained the item separation index H = 3.81.IDEvaluasi adalah bagian dan tahapan penting yang harus dilalui pendidik untuk menjamin pembelajaran efektif. Hasil evaluasi dapat dijadikan bahan refleksi guru dalam mengembangkan dan menyelenggarakan program dan kegiatan pembelajaran. Penelitian bertujuan untuk membandingkan analisis penilaian atau evaluasi menggunakan Teori Tes Klasik dengan Model Rasch dan dapat mengetahui perbedaan analisis dengan menggunakan kedua model tersebut. Jenis penelitian pada penelitian ini yakni metode kualitatif secara pendekatan deskriptif. Sampel yang digunakan yakni hasil ulangan harian BAB Virus dengan jumlah butir soal sejumlah 15 soal. Analisis penilaian berdasarkan teori tes klasik menggunakan aplikasi Microsoft Excel dan analisis penilaian berdasarkan Model Rasch menggunakan aplikasi Winsteps . Analisis validitas pada teori tes klasik serta Model Rasch berjumlah sembilan soal valid serta tidak valid enam soal, dan valid lima soal serta tidak valid 10 soal. Analisis Uji Reliabilitas melalui teori tes klasik diperoleh nilai sebesar 0,672 dengan kategori sedang serta dari Item Reliability diperoleh nilai 0,87 dengan kategori bagus. Rerata tingkat kesulitan soal pada teori tes sebesar 0,463 pada tingkat sedang, menurut model Rasch terdapat tiga soal sangat mudah, mudah lima soal, sulit tiga soal serta sangat empat soal. Analisis daya pembeda berdasarkan teori tes klasik yang berada pada kategori buruk satu item, enam butir cukup, lima butir tinggi, dan tiga item sangat tinggi. Daya pembeda butir soal berdasarkan Model Rasch diperoleh indeks separasi butir soal H = 3,81.